Formulasi Male Annhilation dan Aroma Buah terhadap Kelimpahan Hama Lalat Buah Hama Cabai di Kabupaten Bangka, Bangka Belitung - Aprillia, Zuria; Saputra, Herry Marta; Pratama, Deni (Politeknik Negeri Lampung., 2026)
Fruit flies (Bactrocera spp.) are among the major agricultural pests attacking chili pepper fruit. The fruit fly species reported to attack chili pepper plants in Indonesia is Bactrocera dorsalis. One method of controlling fruit flies in chili pepper fields is the male annihilation technique (MAT), such as the use of methyl eugenol. Methyl eugenol, a male fruit fly attractant, enriched with fruit aroma in fruit fly traps, was expected to increase fruit fly abundance. This study aimed to determine the abundance of chili pepper fruit fly pests under various combinations of methyl eugenol and fruit aroma. The research was conducted in chili pepper fields in Bangka Regency using a randomized block design with eight replications. The study consisted of six formulations: Methyl Eugenol without fruit aroma (F0); Methyl Eugenol + Chili Aroma (F1); Methyl Eugenol + Starfruit Aroma (F2); Methyl Eugenol + Orange Aroma (F3); Methyl Eugenol + Guava Aroma (F4); and Methyl Eugenol + Mango Aroma (F5). The fruit fly trap model used was the Lynfield trap, and each formulation was mixed with an insecticide containing deltamethrin as the active ingredient. The results identified four fruit fly species: Bactrocera albistrigata, B. carambolae, B. dorsalis, and B. umbrosa, as well as one non-fruit fly species, Ankylopterix cf. anomala. Attractant formulation had no significant effect on fruit fly abundance in chili pepper plants, namely the abundance of B. dorsalis (p = 0.192), B. carambolae (p = 0.203), and the combined abundance of B. dorsalis + B. carambolae (p = 0.259). The methyl eugenol formulation without fruit aroma showed the highest fruit fly abundance compared to the methyl eugenol formulations enriched with fruit aroma, although the difference was not statistically significant. Although not statistically significant, the addition of fruit aroma to methyl eugenol reduced the abundance of B. dorsalis by 32.58–61.80% and reduced the abundance of B. carambolae by 36.71–60.76%. The methyl eugenol formulation without fruit aroma (F0) attracted more male fruit flies than the methyl eugenol formulations enriched with fruit aroma (F1–F5).